Corduroy - Freeman, Don. (New York, Viking Press, 1968)
A toy bear in a department store wants a number of things, but when a little girl finally buys him he finds what he has always wanted most of all.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
3.2
K-3
Keywords: Toys -- Fiction; Fantasy; Picture books; Toys -- Fiction